2016
DOI: 10.3389/fnhum.2016.00635
|View full text |Cite
|
Sign up to set email alerts
|

The Throw-and-Catch Model of Human Gait: Evidence from Coupling of Pre-Step Postural Activity and Step Location

Abstract: Postural activity normally precedes the lift of a foot from the ground when taking a step, but its function is unclear. The throw-and-catch hypothesis of human gait proposes that the pre-step activity is organized to generate momentum for the body to fall ballistically along a specific trajectory during the step. The trajectory is appropriate for the stepping foot to land at its intended location while at the same time being optimally placed to catch the body and regain balance. The hypothesis therefore predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Our study showed smaller reduction in foot-placement error due to support (about through anticipation of CoM trajectory in subsequent steps [24,25]. Differences in the size of effect of crutch support on foot-placement error between target stepping paradigms during walking and a singular step, suggest that balance differentially affects foot-placement control across these two contexts [4,25].…”
Section: Discussionmentioning
confidence: 71%
“…Our study showed smaller reduction in foot-placement error due to support (about through anticipation of CoM trajectory in subsequent steps [24,25]. Differences in the size of effect of crutch support on foot-placement error between target stepping paradigms during walking and a singular step, suggest that balance differentially affects foot-placement control across these two contexts [4,25].…”
Section: Discussionmentioning
confidence: 71%
“…During gait, a brief period of cocontraction/freeze may be functional as it minimally affects the ongoing gait process. This is seen during perturbed gait initiation [339] or when auditory startle responses were elicited during gait [126]. Other different kinds of perturbation can elicit similar brief coactivations of ankle flexors and extensors.…”
Section: Cocontractionmentioning
confidence: 93%
“…Any minor change in the adjustment of the asymmetric step length of the two legs produces dramatic effects in the kinematics, very much as it occurs with minimal changes in the localization of ground reaction forces underneath the feet during the stance phases (6). Therefore, accurate brain control is required for correct rotation of the lower limbs and inversion or eversion of the ankle for successful placement of the foot on the ground (4, 2431).…”
Section: Steering the Body Along Curved Pathsmentioning
confidence: 99%